2010
DOI: 10.1007/s00134-010-1984-4
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ prediction of extubation success

Abstract: Purpose: The spontaneous breathing trial (SBT)-relying on objective criteria assessed by the clinician-is the major diagnostic tool to determine if patients can be successfully extubated. However, little is known regarding the patient's subjective perception of autonomous breathing. Methods: We performed a prospective observational study in 211 mechanically ventilated adult patients successfully completing a SBT. Patients were randomly assigned to be interviewed during this trial regarding their prediction of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
24
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 22 publications
5
24
0
1
Order By: Relevance
“…However, Elsasser et al observed that the built-in commercial ATC may provide adequate inspiratory tube compensation with minimal overassistance (41). This conclusion is further supported by the observation that the reintubation rate in the present study (13.6%) is comparable with that reported from other trials assessing outcome after SBTs (4,6,8).…”
Section: Cart Model -------------------------------------------------supporting
confidence: 92%
See 3 more Smart Citations
“…However, Elsasser et al observed that the built-in commercial ATC may provide adequate inspiratory tube compensation with minimal overassistance (41). This conclusion is further supported by the observation that the reintubation rate in the present study (13.6%) is comparable with that reported from other trials assessing outcome after SBTs (4,6,8).…”
Section: Cart Model -------------------------------------------------supporting
confidence: 92%
“…Adding factors of airway competence (such as cough strength and secretion volume) may have improved the performance of the model. However, in recent studies of extubation outcome (6,8,12,22,24,39), the authors reported that retained secretions and/or weak cough accounted for only 6.2% (range, 0 to 9.9%) of the EFs, which is consistent with the present results. The low frequency of abundant secretions in these studies suggests that a number of years after the increased risk of EF in the presence of copious secretions and weak cough was initially reported, physicians are proficient at extracting principles that emerge from research studies and incorporating them into everyday clinical practice.…”
Section: Cart Model -------------------------------------------------supporting
confidence: 92%
See 2 more Smart Citations
“…In a recent study, successful extubation was twice as frequent among patients who were confident of successful extubation than those who were not confident. 17 Given the many factors involved in respiratory failure, it is unlikely that the art and science of weaning from mechanical ventilation can be distilled to just one equation, or a confident nod. Nevertheless, we eagerly await confirmatory studies that examine the performance of the CORE index in predicting successful liberation of patients from ventilator and airway in a broad population of critically ill patients at multiple centers.…”
Section: See the Original Study On Page 1500mentioning
confidence: 99%